Intestinal parasites in residents from “la canoa” rural community, Anzoátegui state, Venezuela (Revista Venezolana de Salud Pública, 2018)
In February 2013 a cross-sectional study was conducted to determine the prevalence of intestinal parasites in residents from "La Canoa" rural community, located in the south of Anzoátegui state. Voluntary and non-probability sampling was used. Stool samples obtained by spontaneous evacuation were analyzed by direct examination techniques, Kato, spontaneous sedimentation and Kinyoun staining. For statistical data analysis Chi-square test was used (c2) with a safety margin of 95% to demonstrate the independence between the variables studied. Of the 158 people evaluated, 95 were parasitized for a prevalence of intestinal parasites of 60.1%. According to age, all groups were affected without statistically significant difference (χ2 = 8.13 df: 5 p > 0.05). Both genders were equally parasitized (p> 0.05). 46.3 % had polyparasitism and 53.7 % was infected by one only parasite. Eight species of enteroparasites were diagnosed being protozoa (98.9%) more prevalent than helminths (1.1%). Between the protozoa, Blastocystis spp. was the most prevalent parasite with 51.3 %. Attention ws directed to the finding of one case (0.6%) of Entamoeba histolytica /E. dispar/E. moshkovskii complex. Equally noteworthy was the diagnosis of two cases (1.3%) of Cryptosporidium spp. Hymenolepis nana was the only helminth found (0.6%). The most common associations were Blastocystis spp.-Endolimax nana with 13 cases (29.5%) and Blastocystis spp.-Entamoeba coli with 12 cases (25%). To conclude, a high prevalence of intestinal parasites (60.1%) in the "La Canoa" rural community from Anzoátegui state was determined.
Keywords: intestinal parasites; Blastocystis spp; rural community; Anzoátegui